2021
DOI: 10.3389/fpsyt.2021.659288
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Problematic Smartphone Use Severity: Smartphone Use Frequency and Fear of Missing Out as Mediators

Abstract: Problematic smartphone use (PSU) has been linked with stress. Higher levels of stress likely increased problematic smartphone use. We investigated relations between stress, fear of missing out, and problematic smartphone use. The aim of the current study was to analyze the mediating role of fear of missing out (FOMO) and smartphone use frequency (SUF) between stress and PSU. We surveyed a broad sample of 2,276 Chinese undergraduate students in July 2019, using the FOMO Scale, Smartphone Addiction Scale-Short V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 57 publications
2
57
0
2
Order By: Relevance
“…was rated on a five-point scale (from 1 = Not at all true of me" to "5 = Extremely true of me). Applied to Chinese samples, the cultural adaption and reliability of the revised scale are well (40,74,75), and the validity of the revised scale is well (74,76). The goodness of fit [CFI = 0.92, TLI = 0.91, RMSEA = 0.08, 90% CI = (0.07, 0.09)] of confirmatory factor analysis of the Fear of Missing Out Scale in this study indicated that that fit indicators in accordance with the cutoffs recommended in the literature actually showed a satisfactory adequacy, indicating that the scale had good construct validity.…”
Section: Fear Of Missing Out Scalementioning
confidence: 99%
“…was rated on a five-point scale (from 1 = Not at all true of me" to "5 = Extremely true of me). Applied to Chinese samples, the cultural adaption and reliability of the revised scale are well (40,74,75), and the validity of the revised scale is well (74,76). The goodness of fit [CFI = 0.92, TLI = 0.91, RMSEA = 0.08, 90% CI = (0.07, 0.09)] of confirmatory factor analysis of the Fear of Missing Out Scale in this study indicated that that fit indicators in accordance with the cutoffs recommended in the literature actually showed a satisfactory adequacy, indicating that the scale had good construct validity.…”
Section: Fear Of Missing Out Scalementioning
confidence: 99%
“…During the COVID-19 pandemic, smartphones play an essential role in communication, access, and information sharing [2]. Past findings suggest that the COVID-19 pandemic has increased the frequency and dependence of individuals on smartphones [3,4] which might lead to mobile phone addiction among college students [5]. A recent study reported an increased prevalence of mobile phone addiction among students during the COVID-19 pandemic [6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, those suffering from depression, anxiety, and loneliness are at high risk for problematic smartphone use [ 19 , 31 , 35 ]. In a similar vein, as a person’s stress level increases, the possibility of them overusing the internet or their smartphones also increases [ 36 , 37 , 38 , 39 ]. This is because a stressful mental state tends to impair one’s self-control ability and self-efficacy, which makes one prone to problematic behaviors [ 32 , 38 ].…”
Section: Introductionmentioning
confidence: 99%